GENERATION OF ARABIDOPSIS THALIANA LINES WITH SUPPRESSED ATNDA1 UTILIZING RNA INTERFERENCE - Wardiah Wardiah (Universitas Syiah Kuala, 2012)
Atnda1 is one of matrix NAD(P)H dehydrogenase genes in Arabidopsis thaliana. Its function is still unclear. This is an encouragement to study the gene by disrupting the expression of the gene. This study was aimed to generate Arabidopsis thaliana possessing suppressed Atnda1 utilizing RNA interference. Double stranded nda1-RNAi silencing was chosen for this project. The generation of the lines was started by creating specific primer for Atnda1. The creation of nda1-RNAi cassette used the Gateway cloning. We utilized Agrobacterium strain GV3101 as a mediator to transfer the cassette into the plants. Dipping the flower into Agrobactrium solution was done to transfer the nda1-RNAi cassette into wild type Arabidopsis. The seeds collected from the mutant plants were checked in selective media. Contamination was the daunting problem in the process of checking the plants. This was crucial to ensure that the insertion has been done successfully. However, selection of the mutants must be done before analysis of the function is carried on the mutants.